A new dispersed element in the genome of the catfish Hisonotus leucofrenatus (Teleostei: Siluriformes: Hypoptopomatinae) - Ferreira, Daniela Cristina [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Taylor & Francis, 2011)
Eight restriction enzymes were used in the prospection and isolation of repetitive sequences in the genome of the catfish Hisonotus leucofrenatus, a siluriform fish species that presents a large heterochromatic block in the W chromosome. In the tested enzymes, only the BamHI enzyme revealed a distinct band of 224 bp G+C value of 37%. In comparative analyses with sequences already available in the GenBank, the BamHI fragment sequence showed similarity with part of a Lepidoptera transposon. Fluorescent in situ hybridization (FISH) revealed that this sequence presents a dispersed pattern in the genome of H. leucofrenatus, forming clusters in some chromosome pairs in the pericentromeric region, which frequently are rich in constitutive heterochromatin. Based on the analysis performed, it can be inferred that the HLBam fragment constitutes a genomically dispersed transposon type element. It can be considered that the findings in this study can contribute to a better understanding of the organization and distribution of transposable elements in the genome of teleost fish.
Keywords: Fish genome; Fluorescent in situ hybridization; Heterochromatin; Hisonotus leucofrenatus